Cost-effectiveness analysis of offering free leisure centre memberships to physically inactive members of the public receiving state benefits: a case study. (December 2016) - Verhoef, Talitha; Trend, Verena; Kelly, Barry; Robinson, Nigel; Fox, Paul; Morris, Stephen
Abstract Background We evaluated the cost-effectiveness of the Give-it-a-Go programme, which offers free leisure centre memberships to physically inactive members of the public in a single London Borough receiving state benefits. Methods A decision analytic Markov model was developed to analyse lifetime costs and quality-adjusted life-years (QALYs) of 1025 people recruited to the intervention versus no intervention. In the intervention group, people were offered 4 months of free membership at a leisure centre. Physical activity levels were assessed at 0 and 4 months using the International Physical Activity Questionnaire (IPAQ). Higher levels of physical activity were assumed to decrease the risk of coronary heart disease, stroke and diabetes mellitus type II, as well as improve mental health. Costs were assessed from a National Health Service (NHS) perspective. Uncertainty was assessed using one-way and probabilistic sensitivity analyses. Results One-hundred fifty nine participants (15.5 %) completed the programme by attending the leisure centre for 4 months. Compared with no intervention, Give it a Go increased costs by £67.25 and QALYs by 0.0033 (equivalent to 1.21 days in full health) per recruited person. The incremental costs per QALY gained were £20, 347. The results were highly sensitive to the magnitude of mental health gain due to physical activity and the duration of the effect of the programme (1 year in the base case analysis). When the mental health gain was omitted from the analysis, the incremental cost per QALY gained increased to almost £1.5 million. In the probabilistic sensitivity analysis, the incremental costs per QALY gained were below £20, 000 in 39 % of the 5000 simulations. Conclusions Give it a Go did not significantly increase life-expectancy, but had a positive influence on quality of life due to the mental health gain of physical activity. If the increase in physical activity caused by Give it a Go lasts for more than 1 year, the programme would be cost-effective given a willingness to pay for a QALY of £20, 000.